Narrative review of magnetic resonance imaging in quantifying liver iron load - Feng, Qing; Yi, Jixing; Li, Tao; Liang, Bumin; Xu, Fengming; Peng, Peng (Frontiers in Medicine, 2024)
Objective: To summarize the research progress of magnetic resonance imaging (MRI) in quantifying liver iron load. Methods: To summarize the current status and progress of MRI technology in the quantitative study of liver iron load through reviewing the relevant literature at home and abroad. Results: Different MRI sequence examination techniques have formed a series of non-invasive methods for the examination of liver iron load. Theses techniques have important clinical significance in the imaging diagnosis of liver iron load. So far, the main MRI methods used to assess liver iron load are: signal intensity measurement method (signal intensity, SI)[signal intensity ratio (SIR) and difference in in-phase and out-of-phase signal intensity], T2/R2 measurement (such as FerriScan technique), ultra-short echo time (UTE) imaging technique, and susceptibility weighted imaging (including conventional susceptibility weighted imaging)(SWI), quantitative susceptibility mapping (QSM), T2*/R2* measurement, Dixon and its derivative techniques. Conclusion: MRI has become the first choice for the non-invasive examination of liver iron overload, and it is helpful to improve the early detection of liver injury, liver fibrosis, liver cirrhosis and liver cancer caused by liver iron overload.